5 Risk of subsequent injury, crime, and death among individuals hospitalised due to a firearm-related injury. (9th June 2015) - Rowhani-Rahbar, Ali; Zatzick, Douglas; Wang, Jin; Rivara, Frederick
Abstract : Statement of purpose: Annually, 32, 000 deaths, 74, 000 injuries, and 470, 000 violent crimes related to the use of firearms occur in the United States. Hospitalisation may provide a "teachable moment" for interventions that reduce morbidity and mortality; unfortunately, important information on the risk of subsequent injury, crime, and death following a firearm-related hospitalisation (FRH) is currently lacking. We sought to provide this information through a state-wide epidemiologic investigation. Methods/approach: We conducted a retrospective cohort study of all individuals with an injury-related index hospitalisation in 2006–2007 in Washington State. A random sample of all individuals with a non-injury-related hospitalisation frequency matched on age served as the reference group. Probabilistic Methods were used to link the hospitalisation, arrest, conviction, and vital status records within five years before and five years after the index hospitalisation. Cox regression models were employed to compare the risk of rehospitalisation, arrest, conviction, and death across hospitalisation categories defined by the injury mechanism and intent using E-Codes. Analyses were controlled for age, sex, and history of substance abuse, psychiatric disorder, arrest, and conviction. Results: There were 680 FRHs (51% assault, 13% self-inflicted, 28% unintentional, 8% other) among 76, 942 injury-related index hospitalizations. A large proportion of individuals with an FRH were males (86%) and aged 21–30 years (38%). The risk of firearm-related rehospitalisation (hazard ratio [HR] = 25.4; 95% confidence interval [CI]: 9.1–70.8) and death (HR = 6.1; 95% CI: 2.2–17.2), as well as subsequent firearm or violence-related arrest (HR = 3.2; 95% CI: 2.5–4.0) and conviction (HR = 3.3; 95% CI: 2.3–4.6), was significantly greater among individuals with FRHs than those with non-injury-related hospitalisations. Conclusions: FRH is strongly associated with an increased risk of subsequent firearm or violence-related injury, crime, and death. Significance and contributions: Findings provide critical information for developing appropriately-targeted and integrated clinical, criminal justice, and public health interventions to reduce firearm-related morbidity and mortality.